Peran Lembaga Masyarakat Desa Hutan Terhadap Usahatani Kopi Di Desa Curahkalong Kecamatan Bangsalsari Kabupaten Jember - siti nur aini; Herman Cahyo Diartho; Regina Niken Wilantari; Riniati Riniati (Jurnal Ekuilibrium, 2021)
Increasing pressures on the livelihood needs of forest village communities so that utilization of forest resources is also increasing which leads to the destruction of existing forest resources, therefore the government through Perhutani issued a policy to maintain forest sustainability and issued a Community Forest Management Program (PHBM) is forest management system carried out jointly with the sharing of results between Perhutani and forest village communities and interested parties to achieve common interests so that the sustainability of forest functions and the benefits of forest resources can be obtained optimally. To be able to implement the rights and obligations of Community Forest Management (PHBM) the forest village community formed a community organization called the Forest Village Community Institution (LMDH) whose members were required to be a community residing in the village ofkalkalong. Forest management under stands will have an impact on the area which is caused is a reduction in labor unemployment and increase income for forest village communities who use the land under stands for coffee farming in the Bulkkalong Village, Bangsalsari District, Jember Regency.